PENANGANAN KERUSAKAN JALAN OLEH DINAS PEKERJAAN UMUM DAN PENATAAN RUANG KOTA PEKANBARU DI KECAMATAN TAMPAN KOTA PEKANBARU PROVINSI RIAU TAHUN 2019 - Sinurat, Owen; ', Muchid (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Roads have a big function for daily activities. Road maintenance, management and rehabilitation have been stipulated in policy. The implementation of this policy is regulated in the Minister of Public Works Regulation, Number: 13/PRT/M/2011 concerning Procedures for Road Maintenance and Surveillance, and Pekanbaru Mayor Regulation Number 94 of 2016 concerning Position, Organizational Structure, Duties and Functions and Work Procedures of the City PUPR Service Pekanbaru. Tampan Subdistrict is the subdistrict that contributes most to damaged roads in the city of Pekanbaru. In 2019 it became 12.228%. It can be said that the implementation of the duties and functions of the Highways Sector, PUPR Service is not optimal. The aim of the research is to describe the implementation of the duties of the Pekanbaru City PUPR (Highway and Highways) Department in Handling Road Damage in Tampan District in 2019. This research uses regional government management theory regarding management functions by G. R. Terry, Implementation of Government Management. The research approach used is a qualitative approach with descriptive research type. The types and sources of research data are divided into primary data obtained through interviews with informants and secondary in the form of supporting data related to the handling of road damage in Tampan sub-district by the PUPR service. The results of this research are that the handling of road damage in Tampan District in 2019 by the Highways Division of the PUPR service was not optimal. Keywords: Infrastructure, Highways Sector, PUPR Service, Government Management